Defining the Optimal Window for Cranial Transplantation of Human Induced Pluripotent Stem Cell‐Derived Cells to Ameliorate Radiation‐Induced Cognitive Impairment. (12th November 2014) - Acharya, Munjal M.; Martirosian, Vahan; Christie, Lori-Ann; Riparip, Lara; Strnadel, Jan; Parihar, Vipan K.; Limoli, Charles L.
Abstract : The authors report the beneficial cognitive effects of transplanting induced pluripotent stem cell‐derived human neural stem cells in the irradiated rodent brain and how these cells differentiate and mitigate neuroinflammation throughout multiple hippocampal subfields. Given the absence of efficacious treatment options for the devastating side effects of cranial radiotherapy, stem cell therapy may provide a viable solution for this long‐term mental health problem afflicting cancer survivors. Abstract : Past preclinical studies have demonstrated the capability of using human stem cell transplantation in the irradiated brain to ameliorate radiation‐induced cognitive dysfunction. Intrahippocampal transplantation of human embryonic stem cells and human neural stem cells (hNSCs) was found to functionally restore cognition in rats 1 and 4 months after cranial irradiation. To optimize the potential therapeutic benefits of human stem cell transplantation, we have further defined optimal transplantation windows for maximizing cognitive benefits after irradiation and used induced pluripotent stem cell‐derived hNSCs (iPSC‐hNSCs) that may eventually help minimize graft rejection in the host brain. For these studies, animals given an acute head‐only dose of 10 Gy were grafted with iPSC‐hNSCs at 2 days, 2 weeks, or 4 weeks following irradiation. Animals receiving stem cell grafts showed improved hippocampal spatial memory and contextual fear‐conditioning performance compared with irradiated sham‐surgery controls when analyzed 1 month after transplantation surgery. Importantly, superior performance was evident when stem cell grafting was delayed by 4 weeks following irradiation compared with animals grafted at earlier times. Analysis of the 4‐week cohort showed that the surviving grafted cells migrated throughout the CA1 and CA3 subfields of the host hippocampus and differentiated into neuronal (∼39%) and astroglial (∼14%) subtypes. Furthermore, radiation‐induced inflammation was significantly attenuated across multiple hippocampal subfields in animals receiving iPSC‐hNSCs at 4 weeks after irradiation. These studies expand our prior findings to demonstrate that protracted stem cell grafting provides improved cognitive benefits following irradiation that are associated with reduced neuroinflammation.